HAK MASYARAKAT ADAT TERHADAP SUMBER DAYA ALAM LOKAL PULAU KOMODO : QUO VADIS? - Darnia, Meriza Elpha; Hazra, Filza Amalia; Putri, Riau Dela Islami; Ahmad, Nur Hafizah; Hendrik, Muhammad Akbar (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
Natural resources are all types of components found in nature and can be utilized by humans to meet their living needs. In Indonesia, it consists of thousands of islands which are rich in natural resources, especially Komodo Island. The natural resources found on Komodo Island include biological and non-biological resources, where the main biological natural resource there is Komodo. However, along with the government's use of the Komodo Island area, this also has an impact on the indigenous people of Komodo Island, East Nusa Tenggara. This research aims to determine the rights that indigenous peoples should have in managing natural resources in the Komodo Island region. The results obtained from this research are to ensure whether or not the rights of the indigenous people of Komodo Island are fulfilled in addition to the development of the tourism sector on Komodo Island, East Nusa Tenggara. So the success of this research will provide solutions to communities affected by the management of the Komodo Island area. Keywords : Indigenous people; Komodo Island; Natural Resources.